The disposition effect in boom and bust markets - Sabine Bernard; Benjamin Loos; Martin Weber (Leibniz Institute for Financial Research SAFE, 2021)
The disposition effect is implicitly assumed to be constant over time. However, drivers of the disposition effect (preferences and beliefs) are rather countercyclical. We use individual investor trading data covering several boom and bust periods (2001-2015). We show that the disposition effect is countercyclical, i.e. is higher in bust than in boom periods. Our findings are driven by individuals being 25% more likely to realize gains in bust than in boom periods. These changes in investors' selling behavior can be linked to changes in investors' risk aversion and in their beliefs across financial market cycles.
Keywords: D14; G11; G28; 330; Disposition Effect; Financial Market Cycles; Household Finance; Retail Investor